Analisis Efektivitas Penerapan Pajak Hotel Dalam Meningkatkan Pajak Daerah Kabupaten Kubu Raya Kalimatan Barat (Study Kasus Kantor Badan Pendapatan Daerah Kabupaten Kubu) - Amalia, Laila; Prihadini, Diana; Widyatasari, Lusia Wina (Jurnal Ilmu Administrasi Publik, 2024)
Taxes play a crucial role in the development of a region that requires substantial funding for its progress. Taxation is one of the key elements in managing national revenue. Taxes are of utmost importance for the development of a region, as they contribute significantly to its income, as seen in the case of hotel taxes.This research aims to analyze the effectiveness of implementing hotel taxes in boosting local tax revenues in Kubu Raya district. The study employs a qualitative and descriptive approach. The population for this research consists of hotel taxpayers in Kubu Raya district, while the sample comprises the financial reports of local tax revenues in Kubu Raya. The findings of the research indicate that the analysis based on the targets set for 2020-2022 experienced fluctuations and obstacles each year. Moreover, the research revealed that the aspects of efficiency, sufficiency, fairness/equality, responsiveness, and certainty, as proposed by Sugiyono, have not been entirely effective due to various issues. These include inadequate socialization, lack of transparency in reporting income and revenues by taxpayers, and insufficient knowledge among taxpayers about the purpose of analyzing the effectiveness of implementing hotel taxes in enhancing local tax revenues.